Pengaruh Pengenalan Lapangan Persekolahan terhadap Kesiapan Mengajar Mahasiswa - Nisa, Zulfatun (Cendekia: Jurnal Pengembangan Kurikulum dan Pendidikan, 2024)
Readiness to become a teacher is a condition where a person feels ready both physically and mentally to work as a teacher and has the required competencies so as to fulfill all duties and obligations as a teacher. Readiness to become a teacher can be supported by an introduction to the school field. The aim of this research is to analyze the effect of Introduction to the Schooling Field (PLP) on readiness to become teachers as students of the 2023/2024 FAI UNISSULA Islamic Religious Education Study Program. The population of this study were all students of the Islamic Religious Education Study Program participating in the 2023/2024 FAI UNISSULA PLP class, a total of 94 students. The sample size was taken using the Isaac and Michael formula. The sampling technique uses simple random sampling technique. The data collection technique uses a questionnaire. The data analysis methods used are descriptive analysis, classical assumption analysis and simple linear regression test analysis. The results of the research show that there is a positive influence of PLP on the teaching readiness of students in the Islamic Religious Education Study Program at FAI Unissula. The suggestion for this research is that students should increase their readiness to become teachers in terms of physical condition and competence make more use of PLP with more teaching practice.